2017
DOI: 10.1248/bpb.b17-00359
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Unfolded Protein Response by Methylmercury

Abstract: Methylmercury (MeHg) results in cell death through endoplasmic reticulum (ER) stress. Previously, we reported that MeHg induces S-mercuration at cysteine 383 or 386 in protein disulfide isomerase (PDI), and this modification induces the loss of enzymatic activity. Because PDI is a key enzyme for the maturation of nascent protein harboring a disulfide bond, the disruption in PDI function by MeHg results in ER stress via the accumulation of misfolded proteins. However, the effects of MeHg on unfolded protein res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…However, the presence of both toxins suggests a synergistic or, at minimum, additive potential to induce neurodegeneration. Possible mechanisms of combined toxicity may include both BMAA’s and MeHg’s ability to cause glutathione depletion, glutamate dyshomeostasis, mitochondrial dysfunction, and the stimulation of the unfolded protein response [ 15 , 44 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of both toxins suggests a synergistic or, at minimum, additive potential to induce neurodegeneration. Possible mechanisms of combined toxicity may include both BMAA’s and MeHg’s ability to cause glutathione depletion, glutamate dyshomeostasis, mitochondrial dysfunction, and the stimulation of the unfolded protein response [ 15 , 44 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…MeHg is thought to trigger apoptosis via induction of ER stress caused by caspase activation [114,116]. Additionally, we found that S -mercuration of IRE1α interferes IRE1α–XBP1 signaling (Figure 1 [119]). Activation of IRE1α–TRAF2–ASK1 pathway was also observed in XBP1-deficient cells [120].…”
Section: Mehg and Er Stressmentioning
confidence: 87%
“…S4a). In a previous study, we showed that high-dose MeHg blocked XBP1 mRNA splicing in vitro (Hiraoka et al 2017). Thus, we hypothesized that in the late phase of MeHg exposure, the ERAI signal is decreased due to the decline in XBP1 mRNA splicing.…”
Section: Activation Of Upr Branches By Mehg Exposurementioning
confidence: 91%
“…Next, we focused on the transient upregulation of ERAI signaling by MeHg in the somatosensory cortex. We previously showed that XBP1 mRNA splicing is attenuated by exposure to high-dose MeHg, suggesting that IRE1α is a target of S-mercuration (Hiraoka et al 2017). Thus, a decrease in the ERAI signal indicates a decline in XBP1 mRNA splicing or degradation of the ERAI molecule.…”
Section: Activation Of Upr Branches By Mehg Exposurementioning
confidence: 99%
See 1 more Smart Citation